Ground water resource development in hard crystalline rock aquifers on the Nebo Plateau, South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2013)
Dissertation (MSc (Engineering Geology))--University of Pretoria, 2000.